THE PERCEPTION OF TOURISM DEVELOPMENT IN WEST REGION OF ROMANIA - GABRIELA CORINA SLUSARIUC; ILIE RĂSCOLEAN (Annals of the University of Petrosani: Economics)
The main goal of this study is the evaluation of impact perception upon West region of various programmes that have financed the development of touristic projects.